Polo-Like Kinase 1: A Novel Target for the Treatment of Therapy-Resistant Mantle Cell Lymphoma. (21st February 2013) - Ahrens, Adam K.; Chaturvedi, Nagendra K.; Shukla, Ashima; Nordgren, Tara M.; Hegde, Ganapati V.; Vose, Julie M.; Joshi, Shantaram S.
Abstract : Mantle cell lymphoma (MCL) is a B-cell non-Hodgkin lymphoma (NHL) which is one of the most aggressive lymphomas. Despite recent improvements in therapies, the development of therapy-resistance is still a major problem; therefore, in order to understand the molecular basis of therapy-resistance, stable therapy-resistant MCL cell lines have been established by us. Based on the gene expression profiles of these cell lines, Polo-like kinase 1 (PLK1) was chosen as a therapeutic target. In this paper, we demonstrate a significant antilymphoma effect of targeting PLK1 in therapy-resistant MCL cells and primary MCL cells from refractory patients. PLK1 knockdown with the antisense oligonucleotide (ASO)/or small molecule inhibitor BI2536 showed significantly decreased proliferation and increased apoptosis in therapy-resistant MCL cell lines and MCL primary cells. Additionally, the direct protein-protein interaction partners of PLK1 were mapped using ingenuity pathway and confirmed the level of association of these partners with PLK1 based on their expression changes following PLK1 knockdown using real-time PCR. Results suggest that PLK1 is a viable target for the treatment of therapy-resistant MCL.